Deformities prevalence in farmed ballan wrasse (Labrus bergylta) in relation to hatchery origin and life stage - Cavrois-Rogacki, Thomas; Drabikova, Lucia; Migaud, Hervé; Davie, Andrew (Aquaculture, 2021)
The production of farmed ballan wrasse (Labrus bergylta) is developing, with an emphasis on sustainability and quality. However, ballan wrasse hatcheries have anecdotally reported increased prevalence of malformations which may impact on fish welfare and hatchery productivity. The present study therefore aimed to identify and characterise deformities in two of the largest ballan wrasse producers in the UK. A total of 384 farmed fish were sampled at two life stages (post-weaning and pre-deployment) and independent production runs. Additionally, 25 wild caught ballan wrasse were analysed and used as a reference. Each fish was externally examined for malformations including jaw and operculum deformities. The fish were internally examined by x-ray for vertebral deformities and abnormalities of the swim bladder. Mineral analysis of both whole fish and vertebrae were also conducted. The results showed the first information on the ballan wrasse skeleton structure. The total number of vertebrae per fish ranged from 34 to 37, with 37 vertebrae per fish representing 58.2% of all fish analysed. The vertebral column was divided into two regions, namely R1 and R2. R1 included vertebrae 1 to 17 (post-cranial and pre-haemal vertebrae) while R2 included vertebrae 18 to 34–37 (haemal vertebrae and haemal caudal vertebrae). Results showed a high prevalence of vertebrae malformations (up to 33%), jaw/operculum malformations (up to 13.5%) and nephrocalcinosis (up to 25%), with high severity levels in some cases when compared to wild specimens in which malformations were absent. Most malformations were already visible at post-weaning. Wild fish did not show signs of any malformations. Finally, high mineral diets are suggested as a potential route of investigation to reduce the vertebral deformities in ballan wrasse. Increasing the productivity of cleaner fish hatcheries is key to addressing the on-going challenge of sea lice in Atlantic salmon (Salmo salar) farming. It is therefore of paramount importance that the causes of the ...